(untitled) (International Journal of Environmental Sciences, 2025)
The essential oil of Daphne gnidium collected from many sites in Center, East, and West Algeria was obtained through the hydrodistillation of the aerial parts with a low yield (0.01%). Then, we analyzed the essential oils of 04 populations using GC/MS and identified 70 chemical components, with (95.42 % ± 1.09) of total oil on average. The main components of this essential oil are palmitic acid (9.98 ± 3.71 %), linoleic acid (8.34 ± 2.68 %), hexadecanoic acid (7.35 ± 4.35%), carvone (5.67 ± 5.67 %) and spathulenol (5.33 ± 3.90 %). Besides, Daphne gnidium essential oil is rich in fatty acids (25.69 ± 3.21 %), monoterpenes (14.42 ± 3.98 %), and sesquiterpenes (12.85 ± 5.50 %). The hydrocarbons and ketone represent rates of 10.99 ± 6.05 % and 9.14 ± 5. 30 %, respectively. This study allowed identifying many chemotypes in the study populations, namely naphthalene chemotype and nonanal <n-> in the populations of Ouanougha and Zariffet forest, limonene chemotype in the populations of Bibans, and dodecane <n-> chemotype in the populations of Djebel Megress.